Penyuluhan Cara Mendidik Anak Sesuai Dengan Tahap Perkembangan di Dusun Karangmojo, Gunungkidul - Dita Juwita Zuraida; Marlia Tyas Asih; Misbah Fikrianto (Universitas Muhammadiyah Manado, 2024)
Childhood is a golden period in individual development, so understanding the childhood stage is crucial for parents. The first and foremost educators for children are parents. Unfortunately, not all parents have adequate knowledge about how to care for children that is appropriate and in accordance with child development. For example, some parents in Dusun Karangmojo, Gunungkidul, they admit that they still do not understand the stages of child development, both in terms of affective, cognitive, and psychomotor. The purpose of this community service is for parents in Karangmojo Gunungkidul to gain insight into how to educate children according to the stages of child development. Based on the results of the implementation of community service carried out offline to parents in Karangmojo, Gunungkidul, it was found that training activities on how to educate children according to the stages of child development can be useful for participants, in understanding the stages of child development and tips for parenting children according to their age.